Productivity improvement and HR costs reduction through HRIS: A survey on banking industry in Bangladesh - Begum, Halima; Bhuyian, Faruk; Ferdous Alam, A. S. A.; Awang, Abd Hair (2016)
As employee productivity improvement and HR costs reduction are two most effective options of being cost leader, the study aims at examining the relationship between human resource information system (HRIS) and employee productivity and total HR costs based on data extracted from total 40 banks (73%) operating in Bangladesh.HRIS index has been developed based on the responses of HR managers from each bank.The impact of one standard deviation variation of HRIS applications on the employee productivity and total HR costs is calculated through the multiple regression analysis while multivariate analysis of covariance (MANCOVA) is tested to examine the variation of productivity and HR costs according to the ownership patterns where HRIS is taken as covariant.The study found that HRIS improves banks efficiency through improving employee productivity and reducing total HR costs if other things being constant.In addition, employee productivity does not vary according to the ownership patterns of the bank but the state-owned banks have different HR costs experience than private-owned commercial banks in Bangladesh.